Possibilities of violation of ethical principles in sponsored research: analysis, consequences, and prevention measures - Jovan Kulić; Dragana Aksentijević; Ana Kostović; Dejan Krstić; Dragana Branović; Bojan Joksimović; Marija Milić; Stefan Mitić; Siniša Ristić (Биомедицинска истраживања, 2024)
The growing trend of securing private industry funding for biomedical research, particularly from pharmaceutical and medical device companies, has raised significant ethical concerns. Since the 1980s, private industry has become the primary funder of biomedical research, surpassing government funding in the U.S. and other developed countries. This shift introduces potential ethical violations, including hidden conflicts of interest, data manipulation, disregard for ethical guidelines, non-disclosure of negative results, and compromised research independence. These issues can undermine research integrity, compromise patient safety, and erode public trust in scientific findings. Effective measures to prevent ethical violations include strengthening transparency, enhancing research independence, promoting ethical education, and reinforcing regulatory frameworks. By fostering open dialogue, implementing stringent disclosure requirements, and ensuring independent oversight, participants can uphold ethical standards in sponsored research. Addressing these challenges is essential to maintaining the credibility of biomedical research, protecting participant rights, and ensuring that research outcomes reliably contribute to evidence-based medicine and public health.
Keywords: biomedical research; ethics; industry-sponsored research